1997
DOI: 10.1577/1548-8659(1997)126<0477:shombb>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity of Mercury Bioaccumulation by Walleye in Franklin D. Roosevelt Lake and the Upper Columbia River, Washington

Abstract: We examined mercury concentration in muscle of walleye Stizostedion vitreutn from three reaches in Franklin D. Roosevelt Lake, a reservoir on the Columbia River, and from the upper Columbia River, an area contaminated by wastes from metal mining and associated processing activities. Our objectives were to describe the relation between size and age of walleyes and tissue concentrations of mercury and to compare mercury concentrations within a single reservoir system among spatially segregated cohorts. Overall, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Walleye have been reported to contain the highest concentrations of mercury among sport fish species routinely caught in Lake Roosevelt ( Johnson et al, 1988;Serdar, 1993;Munn and Dean, 1995 ). In a study conducted in 1994 by Munn and Dean (1995 ), mercury concentrations in skinned walleye fillet composite samples (n = 34) ranged from 0.11 to 0.44 mg / kg ( wet weight ), with an overall reported mean mercury concentration of 0.34 mg /kg ( SD = 0.07) (Munn and Short, 1997 ). Results of subsequent sampling in 1998 suggest that mercury levels in walleye declined by 59% to a catch -weighted average concentration of 0.17 mg /kg (wet weight ) .…”
Section: Mercury Fish Tissue Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Walleye have been reported to contain the highest concentrations of mercury among sport fish species routinely caught in Lake Roosevelt ( Johnson et al, 1988;Serdar, 1993;Munn and Dean, 1995 ). In a study conducted in 1994 by Munn and Dean (1995 ), mercury concentrations in skinned walleye fillet composite samples (n = 34) ranged from 0.11 to 0.44 mg / kg ( wet weight ), with an overall reported mean mercury concentration of 0.34 mg /kg ( SD = 0.07) (Munn and Short, 1997 ). Results of subsequent sampling in 1998 suggest that mercury levels in walleye declined by 59% to a catch -weighted average concentration of 0.17 mg /kg (wet weight ) .…”
Section: Mercury Fish Tissue Resultsmentioning
confidence: 99%
“…Mercury concentrations in fish and shellfish were obtained for various water bodies from existing data sets (Landolt et al, 1985(Landolt et al, , 1987Johnson et al, 1988;Norecol, 1989;Serdar, 1993;Munn and Dean, 1995;West and O'Neill, 1995;Munn and Short, 1997;O'Neill et al, 1998 ). The mercury concentrations used in this analysis came from the fishery that each specific population was using.…”
Section: Contamination Datamentioning
confidence: 99%
“…It is now believed that current levels of exposure to environmental MeHg are sufficiently high to be chronically toxic to a number of predatory freshwater fish in many environments (Scheuhammer et al, 2007). For example, in some independent field studies, body condition in fish of various species was reported to be inversely correlated with tissue Hg over a range of about 0.1 to 1.0 μg/g ww in liver or axial muscle (Munn and Short, 1997;Cizdziel et al, 2003;Drevnick et al, 2008). In a controlled feeding study, Webber and Haines (2003) reported that golden shiners (Notemigonuscryso leucas), with whole-body Hg concentrations averaging 0.52 μg/g ww, were hyperactive and had altered shoaling behavior relative to fish with lower Hg concentrations.…”
Section: Comparison Of Fish Effect Levels With Mercury Concentrationsmentioning
confidence: 99%
“…For instance, condition was negatively related to whole-body (THg) in yearling yellow perch ($0.03-0.23 mg g À1 wet wt) [40], to muscle (THg) in wild walleye ($0.20-0.38 mg g À1 wet wt) [6], to liver (THg) in northern pike (0.07-0.62 mg g À1 wet wt in muscle) [14], to liver and gonad (THg) in white sturgeon (Acipenser transmontanus; 0.020-0.780 mg g À1 wet wt in liver) [10], and to liver, muscle, and blood (THg) in striped bass (Morone saxatilis; 0.06-1.06 mg g À1 wet wt in muscle) [9]. The relationship between MeHg and fish condition can be confounded by relationships between condition and fish age in some field studies [41], and a weak positive relationship existed in the present study between perch condition and age.…”
Section: Conditionmentioning
confidence: 99%
“…Moreover, the majority of studies that do report MeHg effects on wild fish focus on areas with direct industrial contamination [6,7], or rivers and reservoirs impacted by human actions [8][9][10]. Throughout North America, however, many fish populations inhabit aquatic systems that are remote from human activities, but have whole-body MeHg concentrations (e.g., [11,12]) that exceed the 0.2 mg g À1 wet weight (whole body) threshold that has been proposed to be protective of fish health [13].…”
Section: Introductionmentioning
confidence: 99%